2020
DOI: 10.33394/jk.v6i2.2639
|View full text |Cite
|
Sign up to set email alerts
|

Modul Dinamika Partikel Terintegrasi Permainan Tradisional Berbasis E-Learning untuk Meningkatkan Literasi Sains

Abstract: This research is aimed to develop a particle dynamics module integrated traditional games that is applied in e-learning to improve scientific literacy skills. This study was a developmental research because it developed a module based on local wisdom with the R and D method developed by Borg and Gall. Research procedures included preliminary studies, product planning, product development, product validation (validation by experts), product revisions and field tests. Field trials used one group pretest-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
0
8
0
8
Order By: Relevance
“…Several previous studies have shown the positive impact of implementing the PjBL model, including the implementation of PjBL as a solution for learning in pandemic era [17], a very impressive positive impact on learning outcomes from project learning [12], [18][19][20], Moodle-based PjBL implementation [21], development of PjBL-based student worksheets [22] and critical thinking analysis through PjBL [23]. In addition, previous researchers have also developed interactive e-modules on social studies learning [24], multirepresentation-based e-module [25], chemistry module based on local wisdom of the city of Semarang [26], traditional game integrated module [27], and e-modules to support the 2013 curriculum [28]. The focus of this research is to develop an e-module based on Belitang local wisdom with the PjBL model.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have shown the positive impact of implementing the PjBL model, including the implementation of PjBL as a solution for learning in pandemic era [17], a very impressive positive impact on learning outcomes from project learning [12], [18][19][20], Moodle-based PjBL implementation [21], development of PjBL-based student worksheets [22] and critical thinking analysis through PjBL [23]. In addition, previous researchers have also developed interactive e-modules on social studies learning [24], multirepresentation-based e-module [25], chemistry module based on local wisdom of the city of Semarang [26], traditional game integrated module [27], and e-modules to support the 2013 curriculum [28]. The focus of this research is to develop an e-module based on Belitang local wisdom with the PjBL model.…”
Section: Introductionmentioning
confidence: 99%
“…Semakin aktif peserta didik akan berpengaruh pada hasil belajar. Hasil belajar juga berkaitan erat dengan literasi sains peserta didik (Hadisaputra, et al, 2019;Shofiyah, et al, 2020).…”
unclassified
“…Pengembangan literasi sains sejak dini akan bermanfaat sebagai bekal peserta didik dalam menghadapi tantangan pada kompetensi abad 21 (Wulandari, 2019;Parno et al, 2020). Dengan kata lain, literasi sains atau dalam istilah asing disebut scientific literacy memiliki peran penting dalam membangun generasi muda Indonesia agar memiliki pemikiran serta sikap ilmiah (Shofiyah, Wulandari and Setiyawati, 2020).…”
Section: Hasil Dan Pembahasanunclassified